α-Amylase inactivation by temperature during starch hydrolysis - Apar, DK; Özbek, B (ELSEVIER SCI LTD, 2004)
The work reported here investigates the effects of temperature on the enzymic hydrolysis of corn, rice and wheat starch. Three commercial alpha-amylases. from Bacillus sp., Aspergillus oryzae and Bacillus licheniformis were used for starch hydrolysis. For each starch hydrolysis process, the residual starch concentration and the residual alpha-amylase activity (%) were investigated at temperature of 50 and 60 degreesC depending on the processing time in a stirred batch reactor. Mathematical models were derived using experimental data of residual concentration of each starch used. Some inactivation models were tested to gain an understanding of the relation between temperature and enzyme stability during hydrolysis for each enzyme used. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: corn; rice and wheat starch hydrolysis; alpha-amylase; inactivation; temperature; processing time; mathematical modelling; stirred batch bioreactor; WHEAT-STARCH; KINETICS; ENZYMES; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology; Engineering